Fresh or dehydrated spineless cactus in diets for lambs - Andrade, Solano Felipe Just de; Batista, Ângela Maria Vieira; Carvalho, Francisco Fernando Ramos de; Lucena, Rodrigo Barros de; Andrade, Rafael de Paula Xavier de; Lima Júnior, Dorgival Morais de (Acta Scientiarum. Animal Sciences, 2016)
The objective was to evaluate the effect of partial or total replacement of Tifton 85 hay with fresh or dehydrated spineless cactus on performance and body weight components of sheep. Thirty hair lambs, with 19 kg ± 0.35 kg initial weight, were randomly divided into five treatments, namely: Tifton 85 Hay (HA); Tifton 85 Hay + fresh spineless cactus (HAFC); Tifton 85 Hay + dehydrated spineless cactus (HADC); fresh spineless cactus (FC); dehydrated spineless cactus (DC). In addition to the spineless cactus and hay, the complete mixture contained soybean meal, mineral salt and limestone in all treatments. Animals were confined for 75 days and then slaughtered. The weight of body components was recorded. Dry matter intake, total digestible nutrients intake and voluntary water intake were higher (p < 0.05) for the DC and HADC treatments. The average daily gain was 118 g day-1 and body weight at slaughter of 25.8 kg were not influenced (p > 0.05) by treatments. The cold carcass weight, rib eye area, weight and yield of the skin, liver, kidney and large intestine were higher (p < 0.05) for the DC and HADC treatments. Partial or total replacement of Tifton 85 hay with fresh or dehydrated spineless cactus, in complete diets for sheep, increases the weight of the cold carcass and non-carcass components.